1990
DOI: 10.1016/s0886-3350(13)80796-1
|View full text |Cite
|
Sign up to set email alerts
|

In situ fracture

Abstract: A new technique of phacoemulsification is described in which the nucleus is fractured within the capsular bag (in situ). The characteristics of this technique include hydrodissection, division of the nucleus into quadrants, and manipulation of each quadrant into the safe central zone for emulsification. The advantages of this method are safety, speed, and usefulness in almost all degrees of nuclear density and in small undilatable pupils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(27 citation statements)
references
References 2 publications
0
21
0
6
Order By: Relevance
“…Sodium hyaluronate (1% Healon A ) was injected and a 5 mm continuous circular capsulorhexis (CCC) was made. After hydrodissection, bimanual endocapsular phacoemulsification (AMO Phaco Plus A , Allergan Humphrey) was accomplished through a 3.2 mm incision using the cracking technique (Shepherd 1990). Thorough cortex irrigation and aspiration (I/A) was performed using balanced salt solution (BSS Allergan Endosol A ) with 0.3 mg of epinephrine per 500 ml BSS.…”
Section: Methodsmentioning
confidence: 99%
“…Sodium hyaluronate (1% Healon A ) was injected and a 5 mm continuous circular capsulorhexis (CCC) was made. After hydrodissection, bimanual endocapsular phacoemulsification (AMO Phaco Plus A , Allergan Humphrey) was accomplished through a 3.2 mm incision using the cracking technique (Shepherd 1990). Thorough cortex irrigation and aspiration (I/A) was performed using balanced salt solution (BSS Allergan Endosol A ) with 0.3 mg of epinephrine per 500 ml BSS.…”
Section: Methodsmentioning
confidence: 99%
“…In a paper by Wong et al, 9 the authors evaluated the difference in the duration and power of phacoemulsification required between the in situ fracture variation of divide and conquer (DC) nucleofractis as described by Shepherd 10 and the phaco chop (PC) technique, a variation of divide and conquer nucleofractis in which nuclei are divided into fragments with a phaco chopper instrument without the use of central sculpting, as described by Koch. 11 They found that PC required significantly less (Po0.001) phaco time in minutes (mean ¼ 1.2, standard deviation ¼ 0.79, n ¼ 62) than DC (mean ¼ 2.4, standard deviation ¼ 0.74, n ¼ 55). Other researchers wish to investigate whether they can identify comparable improved outcomes and, in the preparation of their Research Proposal, are asked to perform a power calculation to assess the sample numbers required in each experimental group.…”
Section: Continuous Datamentioning
confidence: 99%
“…As técnicas comparadas neste estudo se diferenciam principalmente pela maneira de fragmentar o cristalino. No grupo 1 (técnica de "dividir e conquistar" de Shepherd, 1990), a fratura ocorre após a confecção, às custas da vibração ultra-sônica da ponteira, de 2 sulcos centrais em cruz no núcleo, de espessura suficientemente tênue que permita a fratura do núcleo em 4 quadrantes, ao se impor, com a ponteira e a espátula, pressões laterais nos sulcos separando os quadrantes (25,(33)(34)(35) . No grupo 2, "quick chop" (4)(5)(6) , utiliza-se ultra-som por frações de segundos juntamente com vácuo elevado para apreender e reter o núcleo à ponteira.…”
Section: Discussionunclassified
“…Os fatores associados à perda de células endoteliais corneanas causada pela facoemulsificação são vários e incluem o tempo de ultra-som utilizado na cirurgia, a turbulência de líqui-do na câmara anterior e o trauma mecânico (17)(18)(19)(20)(21)(22) . A técnica de "dividir e conquistar", modificada por Shepherd em 1990, é bastante popular por ser bem sistemática, utiliza maior quantidade de ultra-som do que a de "quick chop" e não necessita de vácuo tão elevado (23)(24)(25)(26) . Crema em 1996 verificou que a redução da densidade celular endotelial corneana por essa técnica é pequena e, por conseguinte, segura (8) .…”
Section: Introductionunclassified
See 1 more Smart Citation